Metallurgical industrial production development in Russia - D. M. Kucheryavenko (Вестник университета, 2024)
The article presents an analysis aimed at assessing the most important performance indicators related to the production process development in the metallurgy sector of the domestic industry.   The paper considers the imposed anti-Russian sanctions, as well as the period characterized by the negative impact of the COVID-19 pandemic on the country’s industrial production development with a special focus on the metallurgical industry. Through a detailed analysis, the author focuses on key indicators that effectively reflect the Russian metallurgy progression. The dynamics of metallurgical exports to various world markets has been examined. The data obtained and conclusions of the study provide a clear picture of the Russian metallurgy state in a complex geopolitical environment and healthcare crisis conditions.